The effect of rikkunshito on gastrointestinal symptoms and gastric motor function: The first study in a Belgian functional dyspepsia population. Issue 2 (14th October 2019) - Masuy, Imke; Carbone, Florencia; Holvoet, Lieselot; Vandenberghe, Alain; Vanuytsel, Tim; Tack, Jan
Abstract: Background: Rikkunshito, a traditional Kampo medicine, has shown efficacy to treat functional dyspepsia (FD) in controlled trials in Japan. Its putative benefit for European patients and mechanism of action has not been established. Methods: This study examined the effect of rikkunshito on gastric motility and GI symptom perception in FD‐PDS patients in a randomized, placebo‐controlled, cross‐over study. After a 2‐week run‐in period, patients received rikkunshito or matching placebo (2.5 g t.i.d.) for 4 weeks, separated by a 4‐week washout period. Symptoms were assessed by the Leuven Postprandial Distress Scale (LPDS) diary throughout the study. At baseline and after both treatment arms, intragastric pressure (IGP) was measured to evaluate gastric accommodation and gastric motility. Simultaneously, GI symptoms were scored on a 100 mm visual analogue scale. Validated symptom questionnaires (PAGI‐SYM, VSI, DSS, and PHQ) were completed each study visit. Key Results: Twenty‐three patients completed the study (33 ± 14 years, 22.7 ± 3.22 kg/m 2 ). Intragastric pressure was numerically, but not significantly, lower after rikkunshito compared with baseline and placebo ( P = .14). No differences were found in gastric accommodation, nutrient volume tolerance, and symptoms assessed during IGP measurements. Early satiation and postprandial fullness (daily diary) decreased after rikkunshito compared with baseline ( P < .041 for both). Placebo also improved most other symptoms assessed. No significant changes in VSI scores occurred. No adverse reactions occurred. Conclusions: Rikkunshito did not alter gastric motility. Treatment with rikkunshito improved upper GI symptoms in FD patients but similarly high placebo effects were observed using the LPDS diary, PAGI‐SYM, SF‐NDI, and DSS scores. Rikkunshito was safe and well‐tolerated. Abstract : Rikkunshito, a traditional Kampo medicine, has shown efficacy to treat functional dyspepsia (FD) in controlled trials in Japan. In a randomized, placebo‐controlled, 4‐week treatment cross‐over study in Belgian FD patients, intragastric pressure was numerically, but not significantly, lower after rikkunshito compared with baseline and placebo. Early satiation and postprandial fullness decreased after rikkunshito compared to baseline. Rikkunshito was safe and well‐tolerated.